Coloniality has evolved once in Stolidobranch Ascidians - Zeng, L.; Jacobs, M. W.; Swalla, B. J. (Integrative and Comparative Biology, 2006)
Ascidians exhibit a rich array of body plans and life history strategies. Colonial species typically consist of zooids embedded in a common test and brood large, fully developed larvae, while solitary species live singly and usually free-spawn eggs that develop into small, undifferentiated larvae. Ascidians in the order Stolidobranchia include both colonial and solitary species, as well as several species with intermediate morphologies. These include social species, which are colonial but do not live completely embedded in a common test, and a few solitary species that brood embryos and larvae until they are competent to metamorphose. We examined how many times coloniality has evolved within the Stolidobranchia, with phylogenetic analyses using full-length 18S rDNA and partial cytochrome oxidase B sequences for taxa in the families Molgulidae, Styelidae, and Pyuridae. Tunicata orders Phlebobranchia and Stolidobranchia are sister groups, and the family Molgulidae is a monophyletic group and should be raised to the subordinal level, as shown previously by analyses from this lab with partial 18S sequences. In contrast to previous studies, styelids and pyurids are separated into monophyletic groups by ML and Bayesian analyses. We show a single clade within the family Styelidae that contains two colonial (compound) botryllid species, a Symplegma (colonial compound), a colonial (social) species Metandrocarpa taylori, as well as four solitary species, thus confirming that the botryllids are a subfamily of the Styelidae. These results suggest that the ancestor of the Stolidobranchia was solitary and that coloniality has evolved only once within this clade of ascidians. Further phylogenetic analyses of aplousobranch and phlebobranch ascidians will be necessary to understand the number of times that coloniality has evolved within the class Ascidiacea.